2014
DOI: 10.1071/wr14059
|View full text |Cite
|
Sign up to set email alerts
|

How many are there? The use and misuse of continental-scale wildlife abundance estimates

Abstract: The number of individuals in a wildlife population is often estimated and the estimates used for wildlife management. The scientific basis of published continental-scale estimates of individuals in Australia of feral cats and feral pigs is reviewed and contrasted with estimation of red kangaroo abundance and the usage of the estimates. We reviewed all papers on feral cats, feral pigs and red kangaroos found in a Web of Science search and in Australian Wildlife Research and Wildlife Research, and related Austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Unverified continental-scale estimates reported in the literature ranged from 3.8 to 18.4 million cats (Hone & Buckmaster, 2014). Based on the land area of Australia, Hone and Buckmaster (2014) suggested that the commonly quoted estimate of ∼5-18 million cats may have been extrapolated using density estimates from a single location. In 2017, empirical modeling using 91 density estimates from across the continent estimated that the true number of feral cats in Australia is likely considerably lower, ranging from ∼2.1 to 6.3 million (Legge et al, 2017).…”
Section: How Many Million?mentioning
confidence: 99%
See 1 more Smart Citation
“…Unverified continental-scale estimates reported in the literature ranged from 3.8 to 18.4 million cats (Hone & Buckmaster, 2014). Based on the land area of Australia, Hone and Buckmaster (2014) suggested that the commonly quoted estimate of ∼5-18 million cats may have been extrapolated using density estimates from a single location. In 2017, empirical modeling using 91 density estimates from across the continent estimated that the true number of feral cats in Australia is likely considerably lower, ranging from ∼2.1 to 6.3 million (Legge et al, 2017).…”
Section: How Many Million?mentioning
confidence: 99%
“…When the Threatened Species Strategy targets were developed, there was no reliable estimate of the number of feral cats in Australia. Unverified continental‐scale estimates reported in the literature ranged from 3.8 to 18.4 million cats (Hone & Buckmaster, ). Based on the land area of Australia, Hone and Buckmaster () suggested that the commonly quoted estimate of ∼5–18 million cats may have been extrapolated using density estimates from a single location.…”
Section: How Many Million?mentioning
confidence: 99%
“…Nonetheless, there have been pleas for more rigorous attempts at estimating rather than guessing density (Hone & Buckmaster, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, density and other attributes are especially difficult or expensive to estimate for mobile or cryptic species. Nonetheless, there have been pleas for more rigorous attempts at estimating rather than guessing density (Hone & Buckmaster, 2015 ).…”
Section: Introductionmentioning
confidence: 99%